Individual Characteristics and Work Environment in an Effort to Encourage Improved Employee Performance at PT Siraj Badawi Cukup Rupiah - Abel Celani; Feby Amanda Putri; Noveria Susijawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study focuses on individual characteristics and work environment to encourage increased employee performance at PT Siraj Badawi Cukup Rupiah, located in Cirebon Regency. The purpose of this study is to identify various factors that can improve employee performance. The type of research used is associative research with a quantitative approach, with multiple linear regression analysis. The population in this study took the object of all permanent employees of PT. Siraj Badawi Cukup Rupiah, totaling 151 employees, was also used as a sample. The data collected were analyzed using SPSS software to test the regression model and the relationship between variables. The results showed that individual characteristics have a significant influence on employee performance, as well as the work environment, which also has a significant effect on employee performance. This study confirms that positive individual characteristics can create a more supportive work environment and increase work effectiveness. And it is expected to contribute to the understanding of the relationship between individual characteristics, work environment, and provide strategic implications for management in efforts to improve performance in the company.